Critical Confessions Now
VI, 210 p. 1 illus.
Keywords: This book is based on the postmedieval journal special issue Critical Confessions Now. These chapters on confessions exhibit great diversity and take up different disciplinary approaches by scholars who stand at various stages of their careers. They address not only different time periods but also various linguistic and cultural contexts. Contributors deploy a wide array of methods, critical approaches, and narrative voices, and contributors assumed the confessional voice with a whole host of affective responses — from enthusiasm to cautious hesitation to outright discomfort. Previously published in postmedieval Volume 11, issue 2-3, August 2020.